Giant magnetooscillations of the Josephson current: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Gor`kov, L. P.; Kresin, V. Z. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Josephson current flowing through an antiferromagnetic metallic barrier is studied. We consider the most interesting case of the spin-valve structure when the barrier is formed by ferromagnetic layers ordered antiferromagnetically in the direction perpendicular to the current. The most remarkable feature is an appearance of giant magnetooscillations of the current amplitude.